Symposium 12: Information Society Studies in Practice – a Networked Learning Case Study: Symposium Introduction - Pinter, Robert (Proceedings of the International Conference on Networked Learning, 2008)
This symposium contains four papers and focuses on teaching information society in traditional and networked learning in four European countries. The results introduced in the symposium are based on the work of the NETIS consortium (Network for Teaching Information Society), a project supported by the European Union under the Leonardo da Vinci Programme. NETIS is developing a course book and textbook and organising classes in four participating countries to test its materials. Symposium members are all representatives from institutes participating in NETIS. The two-year-long NETIS project ends in November 2008 and the Networked Learning Conference is one of the main events to present the findings of the project. Symposium participants will introduce the NETIS project in general (Pinter), present the findings from the student’s (Sadler and Kalvet) and teachers perspective (Bessenyei and Stoffa) and finally summarise the experiences of the project regarding multicultural diversity in networked learning (Siakas). For more details on the NETIS project and on the presentations in the symposium in general see the abstract and paper of Pinter.